Observable Hysteresis at Low Temperature in “Hysteresis Free” Organic–Inorganic Lead Halide Perovskite Solar Cells - Trystan Watson (The Journal of Physical Chemistry Letters, 2015)
In this paper we address the JV hysteresis behavior of planar organic–inorganic lead halide perovskite solar cells fabricated using PC60BM as the cathode. At room temperature, these devices exhibit apparently hysteresis free JV scans. We observe that cooling the temperature to 175 K results in the appearance of substantial JV hysteresis. Employing chronoamperometric measurements, we demonstrate that the half-time for the relaxation process underlying this hysteresis slows from 0.6 s at 298 K to 15.5 s at 175 K, yielding an activation energy of 0.12 eV. We further demonstrate that by cooling a cell to 77 K while held under positive bias, we are able to “freeze” the cell into the most favorable condition for efficient photovoltaic performance. We thus conclude that changes to device architecture that appear to remove room temperature JV hysteresis may not remove the underlying process(es), but rather shift them to time scales not readily observable in typical room temperature JV scans.